The Effect of Leadership Style and Intrinsic Motivation toward Organizational Commitment with Job Satisfaction as Intervening Variables at Petukangan Hospital - Assyifa Azizah Fernendes; Rokiah Kusumapradja; Erry Yudhya Mulyani (Jurnal Cinta Nusantara (JCN), 2024)
The hospital is a health facility where health efforts are carried out. The hospital has various units of trained and educated personnel in dealing with medical problems for the recovery and maintenance of patient health. In providing services, medical and non-medical personnel have a very big responsibility for patients and organizations. Employees’ low organizational commitment is serious for Petukangan Public Hospital. Hence, it becomes the main problem in this study. Based on the main problem, this research intends to analyze the effect of leadership style and intrinsic motivation toward organizational commitment through job satisfaction at Petukangan Public Hospital. The research method used was a descriptive quantitative approach. The types of data used were primary data and secondary data. The sample of this research was all medical and non-medical employees at Petukangan Public Hospital with a total of 129 respondents. Research data processing used statistical regression analysis with hypothesis testing and path analysis. The results of the research showed that each independent variable had a significant effect on the dependent variable. Based on the results of the analysis, it was found that leadership style had a significant effect of 0.095 or 9.5%, and the intrinsic motivation variable had a significant effect of 0.291 or 29.1%. The job satisfaction variable had a significant effect of 0.452 or 45.2%. Furthermore, the results of the analysis of the effect of intrinsic motivation through job satisfaction on organizational commitment have a significant effect with a sig value of 0.004. It was less than the sig value of 0.05. Meanwhile, the effect of leadership style through job satisfaction toward organizational commitment did not have a significant effect with a sig value obtained of 0.245 greater than the 0.05 sig value.